2015
DOI: 10.1021/acs.jpcc.5b03290
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 5-(Hydroxymethyl)furfural by Stepwise Dehydration over TiO2 with Water-Tolerant Lewis Acid Sites

Abstract: The reaction mechanism for the formation of 5-(hydroxymethyl)furfural (HMF) from glucose in water over TiO 2 and phosphate-immobilized TiO 2 (phosphate/TiO 2 ) with water-tolerant Lewis acid sites was studied using isotopically-labeled molecules and 13 C nuclear magnetic resonance (NMR) measurements for glucose adsorbed on TiO 2 . Scandium trifluoromethanesulfonate (Sc(OTf) 3 ), a highly active homogeneous Lewis acid catalyst workable in water, converts glucose into HMF through aldose-ketose isomerization betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 48 publications
5
80
3
Order By: Relevance
“…We have previously reported that the conversion of glucose and xylose to HMF and furfural over Lewis acid sites on Nb 2 O 5 and TiO 2 surfaces is based on step‐wise dehydration via the formation of dicarbonyl compounds typically represented by 3‐deoxyglucosone . In the case of glucose conversion, the Lewis acid sites facilitated the subsequent dehydration of 3‐deoxyglucosone to yield HMF as a main product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that the conversion of glucose and xylose to HMF and furfural over Lewis acid sites on Nb 2 O 5 and TiO 2 surfaces is based on step‐wise dehydration via the formation of dicarbonyl compounds typically represented by 3‐deoxyglucosone . In the case of glucose conversion, the Lewis acid sites facilitated the subsequent dehydration of 3‐deoxyglucosone to yield HMF as a main product.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the D-content of the resultant LA could be determined with 2 H NMR in Figure 7 and with the HPLC profile of the reaction mixture to be We have previously reported that the conversion of glucose and xylose to HMF and furfural over Lewis acid sites on Nb 2 O 5 and TiO 2 surfaces is based on step-wise dehydration via the formation of dicarbonyl compounds typically represented by 3deoxyglucosone. [49][50][51] In the case of glucose conversion, the Lewis acid sites facilitated the subsequent dehydration of 3deoxyglucosone to yield HMF as a main product. Although YNbO 4 also converted glucose to 3-deoxyglucosone in the first step, the retro-aldol reaction of 3-deoxyglucosone is more preferable than subsequent dehydration in the next step, which leads to the formation LA as a final product.…”
Section: Resultsmentioning
confidence: 99%
“…Biodiesel synthesis and utilisation of glycerol are also important topics [75,76], though only one process has been industrialised for biodiesel production on ZnO-Al 2 O 3 catalysts. Note that the solid acids and bases applicable to biomass conversions should be water-tolerant catalysts [77,78].…”
Section: Biomass Transformation Reactionsmentioning
confidence: 99%
“…These materials are abundant and cheap, and express water-tolerant Lewis acid sites and tunable acid-base properties with promising glucose-upgrading abilities [31,32]. Recently, we have shown that tungstite (WO 3 ·H 2 O) is also a viable contender [33].…”
Section: Introductionmentioning
confidence: 99%